2022
DOI: 10.3389/fpsyg.2022.892415
|View full text |Cite
|
Sign up to set email alerts
|

Carbon information disclosure quality, greenwashing behavior, and enterprise value

Abstract: As global warming becomes increasingly prominent, countries worldwide advocate for a low-carbon economy to cope with the pressure to reduce greenhouse gas emissions. The Chinese government has proposed a “dual carbon” goal of peaking carbon emissions by 2030 and becoming carbon neutral by 2060. The disclosure of carbon information by Chinese enterprises has attracted widespread attention from society. This study selects the constituents of the Social Responsibility Index of China Shanghai Stock Exchange from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…That is, the future seems to be more distant and distinct to firms with strong FTR languages than it is to firms using weak FTR languages (Chi et al, 2020). Such "short-termism" is expected to induce firms which use strong-FTR languages to be more opportunistic and less concerned about the negative future consequences of their decisions (Kim et al, 2021), thus predisposing these firms to engage in more controversial marketing and environmental practices to maximise near-term benefits (Cao et al, 2022;Sohyun et al, 2022;Tipton et al, 2009). Cheng et al (2022) and other previous studies have demonstrated that firms in countries with strong-FTR languages are more likely to engage in deviant financial practices that maximise short-term performance despite the risk of potential future adverse consequences, such as damage to the corporation's reputation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the future seems to be more distant and distinct to firms with strong FTR languages than it is to firms using weak FTR languages (Chi et al, 2020). Such "short-termism" is expected to induce firms which use strong-FTR languages to be more opportunistic and less concerned about the negative future consequences of their decisions (Kim et al, 2021), thus predisposing these firms to engage in more controversial marketing and environmental practices to maximise near-term benefits (Cao et al, 2022;Sohyun et al, 2022;Tipton et al, 2009). Cheng et al (2022) and other previous studies have demonstrated that firms in countries with strong-FTR languages are more likely to engage in deviant financial practices that maximise short-term performance despite the risk of potential future adverse consequences, such as damage to the corporation's reputation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Such “short-termism” is expected to induce firms which use strong-FTR languages to be more opportunistic and less concerned about the negative future consequences of their decisions (Kim et al. , 2021), thus predisposing these firms to engage in more controversial marketing and environmental practices to maximise near-term benefits (Cao et al. , 2022; Sohyun et al.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In the private sphere, the demand for climate certifications—that is, climate or carbon neutral—is growing, although climate neutrality does not necessarily imply sustainability (Birkenberg & Birner, 2018). Additionally, there is growing mistrust among consumers due to past improper claims and green washing from enterprises (Birkenberg & Birner, 2018; Cao et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As green products are more and more valued by consumers, the marketing of various green products by manufacturers often makes it impossible for consumers to judge whether a product is a green product, causing green confusion. Greenwashing is when a business only promotes its green image without any real green product attributes (Cao et al, 2022). Manufacturers promote their green image without any green product attributes which may confuse consumers' evaluation of circular products.…”
Section: ) Excessively Exquisite Packaging and Greenwash Perceptionmentioning
confidence: 99%